The impact of task complexity on EFL learners' writing production across gender - Mohammad, Mahgoub Kamel Mahmoud; Mandour, Seham; Nik Aloesnita, Nik Mohd Alwi (UTM Press, 2019)
The current study investigates the impact of task complexity on EFL learners' writing production across gender. Task complexity is the inherent cognitive demands of the tasks imposed on the learners by the structure of the tasks. It was investigated along the resource-dispersing variables of Pre-task planning time, post-task editing time and prior knowledge across the task difficulty variable of same gender. It also tries to intertwine the concepts of Task Complexity (i.e. TBLT) and sociolinguistics (i.e. gender issues). The aim of this study is to investigate the effectiveness of task complexity on gender differences of EFL learners' writing production which has been measured in terms of CAF i.e. complexity, accuracy and fluency. This can provide useful information in field of foreign language acquisition for language planners, curricula designers, and teachers. It is believed that it can contribute to improving EFL undergraduate students’ ability to a level of writing competence that is more likely to be satisfactory. The findings of the study suggest that variations of certain types of task complexity (in the design of pedagogic tasks) will have particular effects on attentional resources. Subsequently, the researcher believes that directing these attentional resources may have positive effects on learners’ language production and the ability to learn the target language. Besides, study concluded that there is statistically significant difference between males and females in terms of writing production along task complexity.